2019
DOI: 10.1145/3359183
|View full text |Cite
|
Sign up to set email alerts
|

Dark Patterns at Scale

Abstract: Dark patterns are user interface design choices that benefit an online service by coercing, steering, or deceiving users into making unintended and potentially harmful decisions. We present automated techniques that enable experts to identify dark patterns on a large set of websites. Using these techniques, we study shopping websites, which often use dark patterns to influence users into making more purchases or disclosing more information than they would otherwise. Analyzing ∼53K product pages from ∼11K shopp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
101
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(151 citation statements)
references
References 39 publications
4
101
0
1
Order By: Relevance
“…10 Dark patterns are anything but rare. In a recent largescale study, Mathur et al (2019) tested automated techniques that identified dark patterns on a sizeable set of websites. They discovered 1,818 instances of dark patterns from 1,254 websites in the data set of 11,000 shopping websites.…”
Section: Persuasive and Manipulative Choice Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Dark patterns are anything but rare. In a recent largescale study, Mathur et al (2019) tested automated techniques that identified dark patterns on a sizeable set of websites. They discovered 1,818 instances of dark patterns from 1,254 websites in the data set of 11,000 shopping websites.…”
Section: Persuasive and Manipulative Choice Architecturesmentioning
confidence: 99%
“…In sum, persuasive designs and commercial nudges can go far beyond transparent persuasion and enter the territory of hidden manipulation when they rely on dark patterns (Mathur et al, 2019), default settings that intrude on user privacy (Norwegian Consumer Council, 2018), and the exploitation of people's biases and vulnerabilities (Susser et al, 2019). These practices affect not only how users access information but also what information they agree to share.…”
Section: Persuasive and Manipulative Choice Architecturesmentioning
confidence: 99%
“…Brignull (see Brignull, 2019;Gray, Kou, Battles, Hoggatt, & Toombs, 2018;Mathur et al, 2019) are a manipulative and ethically questionable use of persuasive online architectures.…”
Section: Persuasive and Manipulative Choice Architecturesmentioning
confidence: 99%
“…In sum, persuasive designs and commercial nudges can go far beyond transparent persuasion and enter the territory of hidden manipulation when they rely on dark patterns (Mathur et al, 2019), default settings that intrude on user privacy (Norwegian Consumer Council, 2018), and the exploitation of people's biases and vulnerabilities (Susser et al, 2018). These practices impact not only how users access information but also what information they agree to share.…”
Section: Persuasive and Manipulative Choice Architecturesmentioning
confidence: 99%
See 1 more Smart Citation